“Not Until the Baby Arrives”: When Delusional Pregnancy Impacts the Management of Uterine Cancer - Norys, Marnina; Szego, Michael; Shore, Eliane; Maggi, Julie (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2024)
A 56-year-old postmenopausal woman (FB) was diagnosed with Grade 1 endometrioid adenocarcinoma but was refusing a hysterectomy. The patient understood she had cancer and understood treatment was required to treat the condition. However, due to a well-entrenched delusion of pregnancy associated with a diagnosis of schizophrenia, FB believed the surgery recommended by her gynecologist would harm the fetus she believed to be developing inside her womb. FB was deemed incapable of consenting to surgery due to her pregnancy delusion, which meant that the procedure could be performed with consent from a substitute decision maker (SDM). In this paper, we describe our team’s approach to the presenting moral dilemma consisting of a choice between forcing surgery on an unwilling patient or allowing her to die of a treatable illness.